Making Modern Florida : How the Spirit of Reform Shaped a New State Constitution - Adkins, Mary E. (Book collections on Project MUSE., 2016)
This book examines the history and impact of the 1966-68 revision of the 1885 Florida state constitution; a process in which state citizens took back powers that their forerunners over a century earlier had effectively ceded to the federal government.